2021
DOI: 10.1001/jamanetworkopen.2020.34074
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Toxic Effects Associated With Dose-Fractionated Radiotherapy Among Patients With Cancer and Comorbid Collagen Vascular Disease

Abstract: Key Points Question Is dose-fractionation associated with the incidence of toxic effects among patients with cancer and comorbid collagen vascular disease? Findings In this cohort study of 197 adults with cancer and comorbid collagen vascular disease, the incidence of severe toxic effects was similar across multiple dose-fractionated radiotherapy regimens, including conventionally fractionated, moderately hypofractionated, and ultrahypofractionated radiothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…Surprisingly, the differential choice of PT or CIRT in our series did not affect acute and late toxicity, and the potential higher immunogenicity of CIRT was not related to more complications in patients with an immune system dysregulation such as ADs. In this regard, the straightforward implication is that even the hypofractionated CIRT schedules, compared to the conventional fractionation schemes of PT in our series, did not have an impact on the late toxicity profile, confirming the result on the independence of fractionation reported for conventional RT [23].…”
Section: No G5 Toxicitysupporting
confidence: 85%
See 1 more Smart Citation
“…Surprisingly, the differential choice of PT or CIRT in our series did not affect acute and late toxicity, and the potential higher immunogenicity of CIRT was not related to more complications in patients with an immune system dysregulation such as ADs. In this regard, the straightforward implication is that even the hypofractionated CIRT schedules, compared to the conventional fractionation schemes of PT in our series, did not have an impact on the late toxicity profile, confirming the result on the independence of fractionation reported for conventional RT [23].…”
Section: No G5 Toxicitysupporting
confidence: 85%
“…On the other hand, considering the late side effects, Chen et al reported a significant difference in patients with CVD compared to controls (17% vs. 3%, p = 0.0095) [20], and a trend towards an increased rate of G ≥3 late toxicity (9.3% vs. 3.7%, p =0.079) was found in the paper by Lin et al [22]. Additionally, a recent single-institution retrospective study on 194 patients with CVD treated for cancer reported that a severe acute and late toxicity profile was not correlated with the different RT schedules and dose fractionation regimens (conventional fractionation, moderate hypofractionation and ultra-hypofractionation) [23].…”
Section: Discussionmentioning
confidence: 84%
“…Local therapy using radiotherapy can be given before and after surgery (Baskar et al 2012), and it depended on the clinical condition of the patient, where it can also determine his radiotherapy techniques (Yoon et al 2021). Radiotherapy doses between 45-50 Gy in 25 to 28 times of administration, with integrated doses simultaneously up to a total dose of 57.5 Gy in 25 times of administrations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, hypotreated prostate cancer patients suffered from significantly increased late genitourinary toxicity (106). In contrast, in the latest studies comparing hyperfractionated radiotherapy, conventionally fractionated radiotherapy, and hypofractionated radiotherapy, although relatively lower-fractionated radiotherapy may increase acute toxicity, there appears to be no significant difference in the long-term effects or late toxicity (105,(107)(108)(109)(110)(111)(112). More systematic studies are required to determine whether fractionated radiotherapy is superior to conventional radiotherapy.…”
Section: B) Dose Distributionmentioning
confidence: 99%